Preventing Suicide Behavior using Village Helpers in Post Conflict Northern Uganda - Oboke, Henry; Elklit, Ask; Ovuga, Emilio; Sodemman, Morten (Makerere University College of Health Science, 2017)
Suicide and suicide attempts are world-wide prevalent phenomena causing unnecessary deaths and injuries. Fortunately, these deaths and injuries are preventable through supportive interventions. However, methods and interventions for prevention are diverse and not fully transferable between countries, societies or cultures. This study investigated the feasibility of implementing a protocol for use by trained Village Helpers (VHs) to prevent suicides and suicide attempts in post-conflict Northern Uganda. We recruited and trained 54 VHs (22.2% females and 78.8 % men, age range 22-60 years, median 32 years) to identify and manage psychosocial problems, suicide communication, suicide risk and suicide attempts. The VHs recorded and compared data on all suicides and suicide attempts in 2015 and 2016 in the 54 parishes of Gulu district including reasons for the suicidal behavior against entry point prior to VHs engagement. We found a reduction of 36.8% completed suicides and of 64.9% suicidal attempts between the years of 2015 and 2016. VHs successfully identified and prevented psychosocial problems like conflicts and illnesses that would lead to suicidal behavior at the household level. VHs were also able to adequately counsel and stabilize those who attempted suicide and prevented further attempts in doing so. In conclusion, VHs were able to be trained and use the standardized Village Helper Suicide Prevention Protocol to prevent suicide and suicide attempts in post-conflict Gulu district of Northern Uganda. More research is needed to establish the effectiveness of VHs including studies of persistent problematic aspects of suicidal behavior for effective prevention programs and for generalization to other post-conflict communities.
Keywords: Village helper; Suicide; Suicide attempts; Psychosocial problems; Household level